ALK-Negative Anaplastic Large Cell Lymphoma Presenting as Disseminated Intravascular Coagulation and Hemophagocytic Lymphohistiocytosis: A Potentially Fatal Presentation - Uroosa Ibrahim; Amina Saqib; Maryam Rehan; Jean Paul Atallah (Case Reports in Hematology)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening disorder that can be familial in etiology or a result of infections, malignancy, and autoimmune or inflammatory disorders. Disseminated intravascular coagulation (DIC) is common in patients admitted to intensive care units and can confound and delay the diagnosis of HLH. We present a case of a 69-year-old female who presented with dyspnea and malaise. Her condition declined rapidly with laboratory parameters consistent with DIC. In addition, she had a ferritin of 32,522 ng/mL, low haptoglobin, and elevated LDH, and bone marrow biopsy showed hemophagocytic lymphohistiocytes. She was started on HLH-directed therapy, and later, a diagnosis of ALK-negative anaplastic large cell lymphoma was made on an excisional inguinal lymph node biopsy specimen. Our case emphasizes the importance of prompt recognition, diagnosis, and treatment of HLH while workup for a primary disorder is still being pursued.